A dehydrative arylation and thiolation of tertiary alcohols catalyzed by in situ generated triflic acid - Viable protocol for CC and CS bond formation. Issue 43 (25th October 2018) - Roy, Deblina; Panda, Gautam
Abstract: The title paper discusses a mild strategy for an efficient CC and CS bond formation through ortho -quinone methide intermediate. A total of 29 examples (23 tetrasubstituted methanes with a quaternary carbon center and 6 triarylmethyl thioarenes) with diverse substitution patterns could be prepared in high yields (up to 82%). Use of indium triflate allowed the transformation to be carried out in an open flask without taking special care leaving water as the only by product. Control experiments revealed that the triflic acid generated in situ from indium triflate, probably through the coordination with substrate, acted as the actual catalyst for the transformation. Further this protocol can be utilized for the synthesis of promising bioactives such as CDRI-830 analogues, dihydrochromeno[2, 3- b ]indoles and 9-(1 H -indol-3-yl)-9-phenyl-9 H -xanthen-1-ol. Graphical abstract: